EVOLUTIONARY DEVELOPMENT OF MAJOR CITIES OF THE RUSSIAN FEDERATION: NEW TOOLS FOR TERRITORIAL MANAGEMENT - Glebova,; Berman,; Abramov, (Revista Inclusiones, 2019)
A modern city is a complex multifunctional system concentrating considerable material, financial and labour resources. Cities are the most active adopters and sources of innovation, being the spatial centres of progressive change in all spheres of social life. However, an inseparable part of the history of urbanisation is also the history of cities losing their power and eventually leading a quiet life of local centres of small territories or completely dying out. This is an attribute of the urban cycle pattern. Most of the times, a decline in a city's development rates is incomprehensible for several years and failure to timely address it prevents the city from restoring its previous levels of development. That accounts for the need to analyse the evolutionary development of territories. Importantly, the indicators included in such analysis are primary indicators of urban socioeconomic development and their dynamics are closely linked with the city's image and stability of management.